MASTERING THE TERMINOLOGICAL TOOLS OF THE EDUCATIONAL SPHERE AS AN IMPORTANT COMPONENT OF METHODOLOGICAL LITERACY AND LINGUODIDACTIC COMPETENCE OF A FUTURE ENGLISH TEACHER - Гарапко, Віталія; Теличко, Наталія; Липчанко-Ковачик, Оксана; Гарапко, Мар’яна (SWorldJournal, 2025)
The article examines the theoretical and practical issues of training English foreign language teachers, taking into account current trends in educational reform in Ukraine and global challenges. A key concern is ensuring high-quality professional trainin